Nilai Marxisme dalam Novel Ronggeng Dukuh Paruk Karya Ahmad Tohari - Sari, Septi Kartika; Yanuar, Agregat Illah Nur (Adjektiva: Educational Languages and Literature Studies, 2025)
Social inequality is a persistent phenomenon that continues to draw attention across various academic disciplines. This inequality manifests in different forms of social mobility, such as disparities in education, employment, healthcare access, and political power—none of which are evenly distributed across societal groups. To understand the dynamics of social inequality, it is essential to employ a theoretical framework that can elucidate the structure of social stratification. One such framework is Marxist theory, which critically examines class disparities within society. This study aims to explore Marxist values as reflected in Ahmad Tohari’s novel Ronggeng Dukuh Paruk, focusing on three key aspects: (1) social and economic inequality, (2) alienation, and (3) ideological domination. Employing a qualitative approach, this research adopts a literary study method. The primary data source is the novel Ronggeng Dukuh Paruk by Ahmad Tohari, with data collected in the form of relevant textual excerpts. The data collection technique involved close reading and note-taking. The findings reveal that the novel presents several elements of social and economic inequality, including poverty and underdevelopment in Dukuh Paruk, limited life choices, the exploitation of women, and the commodification of women as economic tools. The theme of alienation is evident in the character Srintil, particularly through her identity crisis and sense of estrangement. Meanwhile, the analysis of ideological domination highlights the influence of traditional beliefs, ancestral worship, and imposed social ideologies within the community depicted in the novel.